Distributional policy effects with many treatment outcomes - Carlos Iván Ca\~nón Salazar (Banco de México, 2016)
Different segments of a population affected by the same policy intervention may have different responses. We study the role of equilibrium effects on explaining these differences. Our case study is the government's extension of guarantees during the Great Recession to certain debt issuers. We extend Athey and Imbens [2006] to a scenario of multiple outcome variables, and identify the counterfactual joint distribution. We find the intervention increased the funding for the treated segments, but at the cost of higher spreads. Finally, these equilibrium effects operate dissimilarly along the segments of the treated group, in the extreme, can produce undesired effects.
Keywords: G01; G23; G28; C24; C4; 330; Interventions; Stigma; Identification; Nonlinear Difference-In-Difference; Copulas